2013
DOI: 10.1093/infdis/jit005
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation and Composition of Cutaneous Microbiota in Diabetic and Nondiabetic Men

Abstract: The feet of diabetic men had decreased populations of Staphylococcus species, increased populations of S. aureus, and increased bacterial diversity, compared with the feet of controls. These ecologic changes may affect the risk for wound infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 38 publications
3
72
2
2
Order By: Relevance
“…39 Similarly, a recent study found that the intact skin microbiota of diabetic patients is more diverse and has a different composition than the microbiota of nondiabetic patients. 58 These ecologic changes are consistent with the decrease of coagulase-negative staphylococci and the increase of Corynebacterium spp. and S. aureus described above.…”
Section: Molecular Tools and Management Of Dfumentioning
confidence: 53%
“…39 Similarly, a recent study found that the intact skin microbiota of diabetic patients is more diverse and has a different composition than the microbiota of nondiabetic patients. 58 These ecologic changes are consistent with the decrease of coagulase-negative staphylococci and the increase of Corynebacterium spp. and S. aureus described above.…”
Section: Molecular Tools and Management Of Dfumentioning
confidence: 53%
“…Chronic wounds, often harbor a high burden of polymicrobials prone to forming biofilms. The composition of biofilms differs according to wound etiology, location and clinical context but is dominated by Staphylococcus, Pseudomonas , and Corynebacterium generas including other anaerobic species 78,82,83 . Persistent polymicrobial infection in wounds has been suggested to contribute to poor healing by provoking a prolonged inflammatory phase secondary to sustained recruitment of pro-inflammatory cells 20,84 .…”
Section: Systemic Biomarkers Associated With Wound Healing Impairmentmentioning
confidence: 99%
“…Cultureindependent analyses of the healthy skin microbiota, based on sequencing of the bacterial small-subunit 16S rRNA gene, allow greater resolution in characterizing microbial community structure and have revealed the great topographical and temporal complexity at this barrier surface (4)(5)(6)(7)(8). Some environmental and host factors have been identified to influence commensal skin microbial communities (9)(10)(11)(12). However, the role of cutaneous immune defense in shaping and maintaining the skin microbial ecosystem is currently unknown.…”
mentioning
confidence: 99%